2021
DOI: 10.1093/milmed/usaa259
|View full text |Cite
|
Sign up to set email alerts
|

Soft Tissue Manipulation May Attenuate Inflammation, Modulate Pain, and Improve Gait in Conscious Rodents With Induced Low Back Pain

Abstract: Introduction Low back pain (LBP) is common in warfighters. Noninvasive interventions are necessary to expedite return-to-function. Soft tissue manipulation, for example, massage, is a method used to treat LBP. Instrument-assisted soft tissue manipulation (IASTM) uses a rigid device to mobilize the tissue. This study explored the effects of IASTM on pain, function, and biomarkers. Methods Sprague-Dawley rats (n = 44) were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
4
14
1
Order By: Relevance
“…Additionally, conditioned medium from fibroblasts subjected to STM-like stimulation promotes differentiation of satellite cells into skeletal muscle myocytes 31 . For certain pro-inflammatory mediators such as IL-6 and IL-8, these in vitro studies are remarkably consistent with the reduction in IL-6 or IL-8 levels observed after massage therapy in humans (soft tissue biopsies 32 and plasma 33 ) and rats (sera 34 ).…”
Section: Soft Tissue Manipulation (Stm) Describes a Collection Of Non-invasive Non-pharmacological Mechanotherapies (Such As Massage Stresupporting
confidence: 76%
“…Additionally, conditioned medium from fibroblasts subjected to STM-like stimulation promotes differentiation of satellite cells into skeletal muscle myocytes 31 . For certain pro-inflammatory mediators such as IL-6 and IL-8, these in vitro studies are remarkably consistent with the reduction in IL-6 or IL-8 levels observed after massage therapy in humans (soft tissue biopsies 32 and plasma 33 ) and rats (sera 34 ).…”
Section: Soft Tissue Manipulation (Stm) Describes a Collection Of Non-invasive Non-pharmacological Mechanotherapies (Such As Massage Stresupporting
confidence: 76%
“…Others have published similar results using other force-based methods. Using a method designed to emulate cross-fiber massage, treatment augmented pain induced by experimental subcutaneous inflammation ( Loghmani et al, 2021 ). A robot-assisted mechanical therapy resembling deep tissue therapy was shown to prevent behavioral and histological markers of muscle damage following experimental stroke ( Sen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eq. (3)(4)(5) explains the quaternion to Euler angle conversions to estimate real-time orientation angles of the device [27][28].…”
Section: A Tilt Orientation Sensing With Respect To Gravitymentioning
confidence: 99%
“…Soft Tissue Manipulation (STM) [ 2 ], [ 3 ], a non-invasive force-based intervention, constitutes an integral part of manual therapy which facilitates treatment of NMSK conditions. It enables a therapist to manually palpate and locate soft tissue restrictions or scar tissues and treat them with externally applied forces in linear or curvilinear fashion, shown to remediate inflammation [ 4 ] and enhance blood flow and vascularity. With the current state-of-the-art STM practice, palpation and treatment are performed either by hand only or using tools made of steel or wood for Instrument-Assisted Soft Tissue Manipulation (IASTM).…”
Section: Introductionmentioning
confidence: 99%